2011
DOI: 10.1126/scisignal.2001936
|View full text |Cite
|
Sign up to set email alerts
|

Protein Arginine Methyltransferase 5 Regulates ERK1/2 Signal Transduction Amplitude and Cell Fate Through CRAF

Abstract: The RAS to extracellular signal-regulated kinase (ERK) signal transduction cascade is crucial to cell proliferation, differentiation, and survival. Although numerous growth factors activate the RAS-ERK pathway, they can have different effects on the amplitude and duration of the ERK signal and, therefore, on the biological consequences. For instance, nerve growth factor, which elicits a larger and more sustained increase in ERK phosphorylation in PC12 cells than does epidermal growth factor (EGF), stimulates P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(96 citation statements)
references
References 55 publications
4
92
0
Order By: Relevance
“…Moreover, decreased KRT 8 and 18 promotes the inactivation of ERK1/2 and apoptosis upon activation of the FAS receptor (62). Interestingly, accumulation of MTA in SK-Hep1 cells led to ERK hyperphosphorylation while expression of MTAP and recovery of control MTA concentration induced ERK dephosphorylation, in agreement with previous observations in melanoma cells, suggesting the regulation of the rat sarcoma-rapidly accelerated fibrosarcoma-ERK pathway by MTA (63). The RAF protein has a PRMT5-specific GlyArgGly motif where R563 is dimethylated symmetrically, favoring its degradation (64).…”
Section: Partial Deletion Of Mtap Increases the Sensitivity To Liver supporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, decreased KRT 8 and 18 promotes the inactivation of ERK1/2 and apoptosis upon activation of the FAS receptor (62). Interestingly, accumulation of MTA in SK-Hep1 cells led to ERK hyperphosphorylation while expression of MTAP and recovery of control MTA concentration induced ERK dephosphorylation, in agreement with previous observations in melanoma cells, suggesting the regulation of the rat sarcoma-rapidly accelerated fibrosarcoma-ERK pathway by MTA (63). The RAF protein has a PRMT5-specific GlyArgGly motif where R563 is dimethylated symmetrically, favoring its degradation (64).…”
Section: Partial Deletion Of Mtap Increases the Sensitivity To Liver supporting
confidence: 89%
“…The RAF protein has a PRMT5-specific GlyArgGly motif where R563 is dimethylated symmetrically, favoring its degradation (64). Accumulation of intracellular MTA inhibits RAF Arg 563 methylation increasing its stability, which might lead to ERK overactivation (48,63).…”
Section: Partial Deletion Of Mtap Increases the Sensitivity To Liver mentioning
confidence: 99%
“…activating serine-threonine phosphatase 1 that leads to the dephosphorylation of SR proteins), proliferation, differentiation and apoptosis; or inhibiting protein and DNA methylation by competing with S-adenosylmethionine for methyltransferases [8,9]. Methylthioadenosine is a selective inhibitor of protein arginine methyltransferase 5 (PRMT5) activity [10,11], which in turn dampens cRAF methylation and degradation; this cRAF being responsible for increasing MEK1-2 and STAT3 phosphorylation [12]. Methylthioadenosine also exhibits immunomodulatory activity by suppressing the production of pro-inflammatory cytokines and enhancing the production of antiinflammatory cytokines through an interaction with the nuclear factor kappa B (NFkB) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the increment or decrement of neuronal differentiation by HRas overexpression or knockdown did not induce proliferation or reduce survival of NSCs, respectively. RTKRas signaling events elicit different biological responses through sustained versus transient activation of downstream effectors (Andreu-Perez et al, 2011). Hence, we measured the activity of HRas, and observed an activation of HRas with its stabilization during differentiation of NSCs.…”
Section: Discussionmentioning
confidence: 98%